Master Students' Perceptions of Using ChatGPT to Support Critical Thinking in Academic Writing - Duta Aisyah Pratiwi; Muhammad Tahir; Yunitari Mustikawati (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2026)
This qualitative case study explores master students' perceptions of using ChatGPT to support critical thinking in academic writing at Universitas Negeri Makassar's English Language Education Program. The integration of artificial intelligence in education has sparked debates about its impact on critical thinking development, particularly in academic writing contexts. Using triangulation methods including observations, interviews, self-reflective journals, and documentation analyzed through Paul and Elder's (2019) critical thinking framework and Hyland's (2018) academic writing framework, this study examines how master students perceive ChatGPT as a supportive tool in their academic writing process. Findings reveal that students maintain positive yet critical perceptions of ChatGPT, viewing it as a valuable brainstorming partner and idea generator that enhances their critical thinking capacity. Students demonstrated strong awareness of ChatGPT's limitations regarding reference accuracy and plagiarism risks, emphasizing the necessity of human verification and critical evaluation. The study concludes that master students perceive ChatGPT as an effective cognitive scaffold that can support critical thinking development when used critically, reflectively, and responsibly, with effectiveness depending on active user engagement rather than passive acceptance of AI-generated outputs.